Historic Fertility Differentials in a Northern Athapaskan Community - Roth, Eric Abella (Culture, 1982)
Historic fertility differentials for the Kutchin Athapaskan population of Old Crow Village, Yukon Territory, were examined to determine the role of natural selection and random genetic drift on the contemporary gene pool. Cohort data were utilized to construct Crow’s Index of Natural Selection for nomadic and sedentary Kutchin time periods. Demographic and genetic information was combined to investigate drift with respect to: 1) the fate of a neutral allele, 2) decay of heterozygosity and, 3) the average half-life of a polymorph. Consideration of the population’s cultural history indicates that neither selection nor drift is the prime determinant of the present gene pool. Rather, reconstruction of historic genealogical relationships indicates the presence of a strong founder effect responsible for the genetic microdifferentiation attributed by earlier researchers to drift.